Exploring sports nutritionists` and players` perspectives of nutrition practice within English professional football during the COVID-19 pandemic - Carter, J. L.; Kelly, A. L.; Williams, R. A.; Ford, T. J.; Cole, M. (Science and Medicine in Football, 2021)
The outbreak of the COVID-19 pandemic, and the subsequent suspension of all football-related activity, caused significant disruption to the daily habits of professional football players and support staff. Even when the most severe restrictions were lifted, strict control measures remained in place which likely continued to impact upon nutrition support and intake of players. Thus, this study aimed to understand how restrictions impacted upon nutrition support within professional football, as well as identify how these experiences could inform future practice. Interviews were conducted with twelve sports nutritionists and twelve male professional football players to explore their perspectives of nutrition provision during the COVID-19 pandemic. Thematic analysis indicated three common outcomes: (a) Sub-optimal Nutrition Provision; (b) Reduction in Time with or Access to Players, and; (c) Adaption of Nutrition Practice and/or Dietary Habits. In sum, football clubs should consider the immediate and short-term impact of COVID-19 restrictive measures as players` transition back to normality. Specifically, clubs should provide sports nutritionists with greater capacity to control the nutrition provision, including portion size and food quality. Looking ahead, sports nutritionists are encouraged to reflect upon the novel opportunities that have emerged and consider how these may enhance long-term practice.